The Use of Diary to Improve the Writing Ability of the English Second Graders at Hamzanwadi University - Rudini Rudini; Hanofi Harianto; Ridwan Ridwan; Zulfa Azizaturrohmi; Selamet Riadi Jaelani (Educatio, 2022)
The research aimed at finding out the use of a diary in improving the writing ability of the English students of Hamzanwadi University. The problems formulated in this research were (1) Is the use of diary effective in teaching writing for the English students of Hamzanwadi University? (2) How effective is using a diary in teaching writing for the English students of Hamzanwadi University? The research design of this study was one group pretest and posttest. The population of this research was the second-semester students of Hamzanwadi University, which consisted of 105 students in 4 classes. The present researcher took class D as the sample that consisted of 20 students. The present researcher generated a simple random sampling by obtaining an exhaustive list of a population and then randomly selecting a certain number of individuals to comprise the sample. A pretest and a posttest were given to the students to collect the data. The result of the data analysis indicated that the mean score of the pretest was 34.86 while in the posttest was 48.00. In testing the hypothesis, the result of the t-test was -9.706. The null hypothesis was rejected, and the alternative hypothesis was accepted. So, it can be said that using a diary was significantly effective in teaching writing.